Comparative analysis of Albanian female volleyball players with anthropometric, performance and hematological parameters - Dhurata, B.; Enkeleida, L. (Science, Movement & Health, 2012)
Purpose. Profile and compare, female volleyball players with anthropometric characteristics, performance indicators and haematological parameters. Methods. 24 subjects of two volleyball teams, from elite and university, were assesses for 5 anthropometric characteristics, 6 performance tests and 10 hematological markers. Results and Discussion Elite players display better values for physical, body composition and generic jump parameters, but lower specific performance abilities than counterpart college players. Blood markers revealed normal mean team values while the RBC shows low or tendent to low values for 5 out of 11 parameters, which call for special attention to anemia problems as well. Conclusion. The results could be used to identify eventual health or performance related problems, help and guide coaches for professional evaluation, selection, as well as for planning of the most appropriate traning programs to better fit the players and the team as a whole.